The Irish Drought Impacts Database (IDID): A 287-Year Database of Drought Impacts derived from Newspaper Archives - Ludlow, Francis (My University, 2024)
Understanding of past droughts has been mostly shaped by meteorological data, with relatively less known about the human aspects of droughts, their socio-economic impacts, as well as choices people make in response to droughts in different environmental and socio-political contexts. The lack of data that systematically record and categorize drought impacts is an important reason for this disparity. In this paper, we present an Irish drought impacts database (IDID) containing 6094 newspaper reports and 11,351 individual impact records for the island of Ireland, covering the period 1733–2019. Relevant articles were identified through systematic searching of the Irish Newspaper Archives, and recorded impacts were categorized using a modified version of the classification scheme employed by the European drought impact inventory (EDII). Drawing on the wealth and diversity of content provided by the newspapers, the IDID database provides information on the documented temporal and geographical extent of drought events, their socio-economic and political contexts, their consequences, mitigation strategies employed and their change over time. The IDID also facilitates analysis of long-term patterns in drought incidence, individual impact categories, as well as detailed insight into the impacts of individual drought events over nearly three centuries of Ireland's history. In addition, by allowing an examination of the coherence between meteorological records and identified impacts, it advances our understanding of the influences that contemporary economic, political, environmental and societal events had on the human experience, perception and impact of droughts. This new open-access database, therefore, provides opportunities for improving understanding of drought vulnerability and is an important step in developing greater capacity to cope with and respond to future droughts on the island of Ireland.
PUBLISHED
Abstract: Understanding of past droughts has been mostly shaped by meteorological data, with relatively less known about the human aspects of droughts, their socio-economic impacts, as well as choices people make in response to droughts in different environmental and socio-political contexts. The lack of data that systematically record and categorize drought impacts is an important reason for this disparity. In this paper, we present an Irish drought impacts database (IDID) containing 6094 newspaper reports and 11,351 individual impact records for the island of Ireland, covering the period 17332019. Relevant articles were identified through systematic searching of the Irish Newspaper Archives, and recorded impacts were categorized using a modified version of the classification scheme employed by the European drought impact inventory (EDII). Drawing on the wealth and diversity of content provided by the newspapers, the IDID database provides information on the documented temporal and geographical extent of drought events, their socio-economic and political contexts, their consequences, mitigation strategies employed and their change over time. The IDID also facilitates analysis of long-term patterns in drought incidence, individual impact categories, as well as detailed insight into the impacts of individual drought events over nearly three centuries of Ireland's history. In addition, by allowing an examination of the coherence between meteorological records and identified impacts, it advances our understanding of the influences that contemporary economic, political, environmental and societal events had on the human experience, perception and impact of droughts. This new open-access database, therefore, provides opportunities for improving understanding of drought vulnerability and is an important step in developing greater capacity to cope with and respond to future droughts on the island of Ireland.
Keywords: drought, impact database, Ireland, newspapers; Making Ireland; Smart & Sustainable Planet; CLIMATE CHANGE; Climate History; Irish History; Environment and housing; History